KAJIAN KUALITAS LINGKUNGAN PERMUKIMAN KAWASAN APO KELURAHAN BHAYANGKARA DISTRIK JAYAPURA UTARA KOTA JAYAPURA - AGUS RAHARJO PEPEKAI (Jurnal Ilmu Pendidikan Indonesia, 2018)
This study aims to identify physical and social environmental conditions in the APO residential area of Bhayangkara Village and to determine the quality of the APO residential environment in Bhayangkara Village.This research method is descriptive analytical with a quantitative approach using secondary data analysis supported by field surveys. Research locations in the APO region of Bhayangkara Regency, North Jayapura Regency, Jayapura Regency. The sample location consists of two  neighborhood association. The unit of analysis in this study consisted of housing units.The results showed that the pattern of settlement in the APO area was concentrated in hilly valleys and hillside with a fairly high building density. The quality of the physical environment of the APO area in Bhayangkara Village has decreased due to the high level of building density indicated by the Building Base Coefficient (CDB) value of 78% and the Environment Friendly Coefficient (EFC) of 6.4%. the social environment is still relatively good, this is indicated by the still interaction between residents living in this region.Keywords: Environmental quality, Settlement, physical environment, Socio-cultural environment.